1982
DOI: 10.1073/pnas.79.7.2211
|View full text |Cite
|
Sign up to set email alerts
|

DNA precursor pool: a significant target for N-methyl-N-nitrosourea in C3H/10T1/2 clone 8 cells.

Abstract: Synchronized C3H/IOTI/2 clone 8 cells were treated in vitro with a nontoxic dose of N-methyl-N-nitrosourea during their S phase. Chromatographic isolation of the deoxyribonucleotide DNA precursor pool and measurement of the precursor content per cell showed that a nucleic acid residue in the precursor pool is 190-13,000 times more susceptible to methylation-than a residue in the DNA duplex, depending on the site of methylation. This conclusion comes from measurements indicating that, for example, the N-i posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0

Year Published

1983
1983
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 23 publications
0
54
0
Order By: Relevance
“…However, the concept of damaged nucleotides as premutagenic agents originated 10 years earlier, when Topal and Baker (92) showed that treating cells with a DNA-methylating agent led to far more methylation of free nucleotides than of nucleotide residues in DNA. Whether those modified nucleotides were subsequently incorporated into DNA in significant amounts has still not been established.…”
Section: Chemical Modification Of Nucleotides As a Premutagenic Eventmentioning
confidence: 99%
“…However, the concept of damaged nucleotides as premutagenic agents originated 10 years earlier, when Topal and Baker (92) showed that treating cells with a DNA-methylating agent led to far more methylation of free nucleotides than of nucleotide residues in DNA. Whether those modified nucleotides were subsequently incorporated into DNA in significant amounts has still not been established.…”
Section: Chemical Modification Of Nucleotides As a Premutagenic Eventmentioning
confidence: 99%
“…8-oxoguanine in DNA readily base pairs with adenine, initiating a transversion mutagenesis pathway. The idea that the damage might actually occur at the nucleotide level originated from the demonstration that free intracellular nucleotides are orders of magnitude more reactive with modifying reagents than are the corresponding nucleotides in DNA 111 . The idea gained impetus with the finding that the mutT gene in E. coli, which counteracts ROS-stimulated mutagenesis, encodes a nucleoside triphosphatase, which preferentially cleaves the oxidized nucleotide 8-oxo-dGTP to the corresponding deoxyribonucleoside monophosphate 8-oxo-dGMP plus pyrophosphate 112 .…”
Section: Sanitation Of Damaged Dntp Poolsmentioning
confidence: 99%
“…A primary oxidative base modification in DNA is the oxidized form of guanine, 8-oxo-7,8-dihydro-2′-deoxyguanosine (8-oxodG)567. Furthermore, purine deoxynucleoside triphosphates (dNTPs) in the nucleotide pool are vulnerable to oxidation leading to oxidized forms of DNA precursors, that is, 7,8-dihydro-8′-oxo-dGTP (8-oxodGTP), 7,8-dihydro-8′-oxo-dATP (8-oxodATP) and 2-hydroxy-2′-deoxyadenosine-5′-triphosphate (2-OH-dATP)8910. Oxidized dNTPs can be incorporated into DNA during DNA replication and repair resulting in deleterious effects111213.…”
mentioning
confidence: 99%